HIGH TIBIAL OSTEOTOMY USING A LOCKING TITANIUM PLATE WITH OR WITHOUT AUTOGRAFTING - Sarman,Hakan (2019)
ABSTRACT Objective: To postoperatively evaluate knee scores, radiological assessment results, deficit correction, patellar height change, bone healing time, and weight bearing time in patients undergoing high tibial osteotomy (HTO) with/without autologous iliac bone grafting. Methods: This retrospective examination of treated controls from a randomized controlled study included 63 knees of 58 patients aged 46–59 years who underwent HTO with locking open wedge osteotomy plates. The patients were divided into two groups: Group A, HTO with autologous iliac bone grafts (n = 31); and Group B, HTO without autologous iliac bone grafts (n = 32). Clinical and radiological data were evaluated prospectively at the preoperative consultation and again at 6, 9, and 12 weeks, 6 months, and 1 year after the surgery (and annually thereafter). Results: There were no significant intergroup differences in the radiological assessment, deficit correction, patellar height change, bone-healing time, and weight-bearing time at any time after surgery. The knee scores changed positively in both groups (p < 0.001). Conclusions: There was no difference in the results of patients undergoing HTO with open wedge osteotomy titanium locking plates with or without autografting, and comorbidities resulting from autografts were eliminated with the use of locking plates. Level of evidence III, Retrospective Study.